Temporal trend of research related to gun violence from 1981 to 2018 in the United States: a bibliometric analysis - Lung-Chang Chien; Maxim Gakh; Courtney Coughenour; Ro-Ting Lin (BMC, 2020)
Abstract Background We aimed to evaluate the variation in gun violence-related research in the US over time to determine if there are meaningful changes in frequency of research at certain time points. Related publications were searched from the Web of Science. Methods We searched articles from Web of Science to collect publication data of gun violence research in three disciplines (clinical sciences, life sciences, and social behavior sciences) from 1981 to 2018. The joinpoint regression approach was applied to evaluate the trend of publication ratio. We also adopted the generalized additive mixed model to compare the publication ratio among the three research disciplines. Results During the study period, each research discipline had a significant decrease in publication ratios, especially social behavioral sciences from 2001 to 2011, with an annual percentage change = − 9.77% (95% CI = − 13.45, − 5.93; p-value < .0001). After combining the three research disciplines, the average change of the publication ratio was significantly increased 9.18% (95% CI = 6.42, 12.01; p-value < .0001) per year from 1981 to 2018. Compared to social behavioral sciences, both clinical sciences and life sciences had a significantly smaller publication ratio. Conclusions Gun violence research exhibited a significant downward trend in publications in the early 2000s, which may be attributed at least in part to limited federal funding, but the publication ratio increased since the 2010s. To enhance the amount of peer-reviewed gun violence research so that research-informed gun violence interventions are more likely to succeed, decision-makers should keep supporting quality research.